Justice League vs Bizarro League - Bright, J. E. (Scholastic Inc., 2015)
"What happens when the Justice League meets the Bizarro League, a team of opposite versions of themselves? Their world gets turned upside down! But whether they like it or not, the Justice League will have to team up with their hilariously clumsy counterparts to defeat Darkseid in this all-new, action-packed adventure!"--Back cover.